'Ivory wave' toxicity in recreational drug users; integration of clinical and poisons information services to manage legal high poisoning - Murray, Douglas B.; Potts, Stephen; Haxton, Carole; Jackson, Gillian; Sandilands, Euan A.; Ramsey, John; Puchnarewicz, Malgorzata; Holt, David W.; Johnston, Atholl; Nicholas Bateman, D.; Dear, James W. (Clinical toxicology (Philadelphia, Pa.), 2012)
Abstract Background. Novel psychoactive substances or 'legal highs' can be defined as psychoactive substances that have been developed to avoid existing drug control measures. Consistency of name, but with change in the content of the product, may cause harm. This could result in clusters of users being poisoned and developing unexpected physical and psychiatric symptoms. We describe such an event and the clinical phenotypes of a cluster of patients poisoned with a novel psychoactive substance in 'ivory wave' and analyze data from the National Poisons Information Service (NPIS) to estimate use across the United Kingdom. In addition, the likely active ingredient in this cluster of 'ivory wave' poisonings was identified. Methods. An analysis of consecutive patients attending the Royal Infirmary of Edinburgh emergency department in July and August 2010 with self-reported 'ivory wave' use was performed. Over a similar time frame, poisons enquiries regarding 'ivory wave' to the UK NPIS, by telephone and via the internet-based TOXBASE® poisons database (www.toxbase.org), were analyzed. A sample of 'ivory wave' powder and biological fluids from poisoned patients were investigated to determine the active ingredient. Results. Thirty four emergency attendances due to 'ivory wave' toxicity were identified. The mean +/− SD (range) age was 28.6 +/− 7.8 (16-44) years. Patients demonstrated a toxidrome which lasted several days, characterized by tachycardia (65%), tachypnoea (76%), dystonia (18%), rhabdomyolysis (96%), leucocytosis (57%), agitation (62%), hallucinations (50%), insomnia (32%) and paranoia (21%). Enquiries to NPIS suggest that 'ivory wave' poisoning occurred throughout the United Kingdom. A sample of 'ivory wave' powder was analyzed and found to contain desoxypipradrol, which was also identified in biological fluids from 4 out of 5 patients tested. Discussion. A cluster of cases presenting after use of a novel psychoactive substance was identified in Edinburgh and desoxypipradrol was identified as the likely cause. It was associated with prolonged psychiatric symptoms as a key feature. This chemical was regulated in response to the wider UK outbreak, which NPIS data suggest was geographically widespread but probably short lived. Conclusion. Novel psychoactive substances can produce significant toxicity and data from poisons centres may be used to indirectly detect new 'legal highs' that are causing clinical toxicity.